The Development of STEM-Based Science Teaching Materials on Simple Electrical Circuit Materials - Astra, I Made; Tumijan, Petrus; Uskenat, Kristina; Henukh, Anderias (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
This study aims to create STEM-based science teaching materials based on simple electrical circuits and determine the feasibility of STEM-based teaching materials. Research and development of the Dick & Carey model is the type of research used. The research process comprises four stages: needs analysis, product design, validation and evaluation, and testing. Material experts, presentation experts, linguists, and graphic experts are all involved in expert validation. Teachers who teach science subjects participate in the product feasibility test. Individual, small group, and field trials assess students’ readability. Expert validation revealed that the content aspect was 97.7 % with a very decent category, the presentation aspect was 97.7% with a very proper category, the language aspect was 85% with a very decent category, and the visual aspect was 80 percent with a worthy category. The science teacher’s feasibility test results showed that the content aspect was 90 % with an excellent category, the presentation aspect was 98.6% with an outstanding category, and the language aspect was 96.7% with a superior category. Students’ readability test results showed an average score of 87.7% in the excellent category. Based on the validation and legibility trials findings, developing STEM-based science teaching materials (Science, Technology, Engineering, and Mathematics) on simple electrical circuit materials is feasible. It can be used as a learning resource.